Effects of Current Collector Materials on Performances of Micro-Tubular Solid Oxide Electrolysers for Splitting CO2. (2nd June 2015) - Kleiminger, Lisa; Kelsall, Geoff H.; Li, Tao; Li, Kang
Abstract : Specific surface areas of micro-tubular solid oxide electrolysers (MT-SOEs) increase with the reciprocal of their lumen diameters. However, this benefit over planar counterparts may be offset by difficulties in fabricating effective current collectors for < 1 mm diameter inner electrodes, causing significant potential losses, decreasing their performance. Hence, the effects were investigated of different current collector materials for the inner cathodes of such SOEs for splitting CO2 . Ohmic area-specific resistances were lowest for silver wire-based compared to nickel wire-based current collectors, due to silver's higher electronic conductivity. However, silver's lower mechanical strength required addition of silver paste for effective connections, but the paste interfered with the electrode process, increasing the area-specific electrode polarization at 1.5 V by > 300% at 700 and 800 °C. Microstructural analysis suggested the silver paste caused partial blockage of surface pores. MT-SOEs with only nickel wire current collectors achieved 1 A cm -2 at 1.5 V.